Survey methods and characteristics of a sample of Aboriginal and Torres Strait Islander and non‐Indigenous people who have recently used methamphetamine: the NIMAC survey. (22nd June 2020) - Reilly, Rachel; Wand, Handan; McKetin, Rebecca; Quinn, Brendan; Ezard, Nadine; Dunlop, Adrian; Conigrave, Kate; Treloar, Carla; Roe, Yvette; Gray, Dennis; Stephens, Jacqueline; Ward, James; et al.
Abstract: Introduction and Aims: There is a need for detailed information on methamphetamine use in Aboriginal and Torres Strait Islander communities. We describe a national survey on methamphetamine use among Aboriginal and Torres Strait Islander people and non‐Indigenous people. Design and Methods: Participants aged 16 years or older who reported using methamphetamine in the past year were recruited for a cross‐sectional survey through 10 Aboriginal Community Controlled Organisations. Surveys were completed anonymously on electronic tablets. Measures included the Australian Treatment Outcomes Profile, the Severity of Dependence Scale, subscales from Opiate Treatment Index and the Kessler 10. A Chronic Stress Scale was used to assess culturally situated chronic stress factors. Results: Of the 734 participants, 416 (59%) were Aboriginal or Torres Strait Islander and 331 (45%) were female. In the previous year, most participants reported smoking (48.7%) or injecting (34%) methamphetamine and 17.4% reported daily use. Aboriginal and Torres Strait Islander people did not differ significantly from non‐Indigenous participants on methamphetamine use patterns (age at first use, frequency of use, main mode of use, injecting risk, poly drug use). Aboriginal and Torres Strait Islander participants felt less able to access health care (32% vs. 48%, P  < 0.001), including mental health services (19% vs. 29%, P  < 0.002), were less likely to report a mental health diagnosis (50% vs. 60%, P  < 0.002) and were more likely to turn to family for support (52% vs. 34%, P  < 0.001). Discussion and Conclusions: We recruited and surveyed a large sample of Aboriginal and Torres Strait Islander people from which we can derive detailed comparative data on methamphetamine use and related health service needs for Aboriginal and Torres Strait Islander and non‐Indigenous Australians.